2020
DOI: 10.3390/app10093274
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of Measurement Uncertainty in a Remote Fetal Monitor

Abstract: The perinatal mortality rate is very high throughout the world. A fetal monitor may be used remotely, and this would tackle the problem of continuous monitoring of high-risk pregnancies. There is evidence that current technology is of low reliability, and, therefore, of low precision to identify fetal health. In medical technological implementation, a safe, efficient, and reliable operation must be guaranteed, and the main problem is that remote fetal monitor gathers just a few samples, so the hypothesis of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The 12 presented papers in this second volume are grouped according to their contributions to the main parts of the monitoring and control engineering scheme applied to human health applications, namely papers focusing on measuring/sensing of physiological variables [5][6][7][8], papers describing health monitoring applications [9][10][11][12], and finally, examples of control applications for human health [13][14][15][16]. As indicated by Aerts [1], it is envisioned that the field of human health engineering is complementary to the field of biomedical engineering as it not only contributes to developing technology for curing patients or supporting chronically ill people, but also covers applications on healthy humans (e.g., sports, sleep, and stress) and thus also focuses on disease prevention and optimizing human well-being more generally.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The 12 presented papers in this second volume are grouped according to their contributions to the main parts of the monitoring and control engineering scheme applied to human health applications, namely papers focusing on measuring/sensing of physiological variables [5][6][7][8], papers describing health monitoring applications [9][10][11][12], and finally, examples of control applications for human health [13][14][15][16]. As indicated by Aerts [1], it is envisioned that the field of human health engineering is complementary to the field of biomedical engineering as it not only contributes to developing technology for curing patients or supporting chronically ill people, but also covers applications on healthy humans (e.g., sports, sleep, and stress) and thus also focuses on disease prevention and optimizing human well-being more generally.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
“…The first series of articles in this SI describes methods for (improved) measuring and/or sensing of health-related physiological signals. The work of Arciniega-Montiel et al [5] contributes to developing methods for improving the measuring reliability of fetal monitors, used in the case of high-risk pregnancies, on the basis of probabilistic models. Al-Halhouli et al [6] demonstrated the feasibility of using a wearable and stretchable inkjet-printed strain gauge sensor for estimating respiratory rate, which is a key vital sign variable in many medical and health applications.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%